1999
DOI: 10.1128/jvi.73.6.4689-4695.1999
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of CD4+T-Cell Responses in Coxsackievirus B3-Induced Myocarditis in Mice

Abstract: Coxsackievirus B3 infection causes significant cardiac inflammation in male, but not female, B1.Tg.Eα mice. This gender difference in disease susceptibility correlates with selective induction of CD4+ Th1 (gamma interferon-positive) cell responses in animals with testosterone, whereas estradiol promotes preferential CD4+ Th2 (interleukin-4 positive [IL-4+]) cell responses. Differences in immune deviation of CD4+ T cells cannot be explained by variation in B7-1 or B7-2 expression. Infection significantly upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…Calzolari (1889) first reported a connection between reproduction and immunology when he observed that male rabbits castrated before sexual maturity had larger thymuses than control animals. Reproductive hormones, in particular androgens with an anabolic effect, can alter immunological responses by altering antigen presentation and cellular apoptosis (Huber et al, 1999). In turn, cytokines can directly affect the hypothalamic-pituitarytesticular axis: IL-1b can suppress rat pituitary luteinizing hormone release (Bonavera et al, 1993), and both IL-1b and TNFa can decrease steroidogenic acute regulatory protein (StAR) gene expression, preventing cholesterol translocation to the mitochondrial membrane of Leydig cells, the primary source of testosterone synthesis in males (Lister and van der Kraak, 2002;Ogilvie et al, 1999).…”
Section: Testosterone As a Unifying Link Between Reproduction Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Calzolari (1889) first reported a connection between reproduction and immunology when he observed that male rabbits castrated before sexual maturity had larger thymuses than control animals. Reproductive hormones, in particular androgens with an anabolic effect, can alter immunological responses by altering antigen presentation and cellular apoptosis (Huber et al, 1999). In turn, cytokines can directly affect the hypothalamic-pituitarytesticular axis: IL-1b can suppress rat pituitary luteinizing hormone release (Bonavera et al, 1993), and both IL-1b and TNFa can decrease steroidogenic acute regulatory protein (StAR) gene expression, preventing cholesterol translocation to the mitochondrial membrane of Leydig cells, the primary source of testosterone synthesis in males (Lister and van der Kraak, 2002;Ogilvie et al, 1999).…”
Section: Testosterone As a Unifying Link Between Reproduction Andmentioning
confidence: 99%
“…The binding of testosterone to androgen receptors on T cells can influence the types and quantity of cytokines they synthesize and release. Some evidence suggests that androgens favor the development of a CD4 þ type-1 phenotype of peripheral lymphocytes and cytokines Giltay et al, 2000;Huber et al, 1999), which may increase susceptibility to certain infections that are cleared via the Th-2 cytokines. Alternative evidence suggests that androgens can diminish proinflammatory cytokine production (specifically IL-1b, TNFa, and IFNg) by macrophages Burger and Dayer, 2002;Grossman et al, 1995;Lin et al, 1996;Smithson et al, 1998;Straub and Cutolo, 2001).…”
Section: In Vitro Experiments Of Testosterone and Immune Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In support, several studies showed that androgen treatment in vitro inhibits inflammatory responses by promoting anti-inflammatory signaling pathways leading to secretion of IL-10 and TGF-b, while the release of pro-inflammatory mediators such as IL-1b, IL-6, or TNF-a was inhibited. 5,[13][14][15][16][17][18] In the testis, androgen levels are substantially higher than in serum, a fact that has been connected with the so-called immune privilege characteristic of this organ. [19][20][21][22] In the testis, immune privilege has been demonstrated by the ability to tolerate alloand xenoantigens experimentally transplanted in this organ.…”
Section: Introductionmentioning
confidence: 99%
“…American Journal of Reproductive Immunology 74 (2015)[12][13][14][15][16][17][18][19][20][21][22][23][24][25] …”
mentioning
confidence: 99%